If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -3 = 0 Reorder the terms: -3 + 2k = 0 Solving -3 + 2k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2k = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2k = 0 + 3 2k = 0 + 3 Combine like terms: 0 + 3 = 3 2k = 3 Divide each side by '2'. k = 1.5 Simplifying k = 1.5
| 2x+2=59 | | 0=-x^2+3 | | -130+3x=113-6x | | -3x+5=x+-5 | | -130+3x=113- 6x | | x^2-2x+6=2x^2-6x-26 | | 9x-83=3x+67 | | 12m^2-32m+20=0 | | X=-x^2+3 | | 7x+5-3x-8=8x+6+5x-9 | | X^2+17x-168=0 | | 1.4x+x=-12 | | 1.6X=6.4 | | 3(x-1)=2(2x+1)-(x+5) | | -6(x+10)=-36 | | 8v^3+1= | | 3x+5x=13 | | -10x*2-24=0 | | 3x*2-12=0 | | 34+h=39 | | 6x^2=6+5x | | -21x=0 | | 2x+5x=28 | | 2x-5x=28 | | 241-2x=43x+21 | | 7-9x=73-23x | | (-16t^2)+31t-14=0 | | [2x+3]=3x+5 | | 0.2x+18.3=x-5.62 | | 3(2x-2.1)=4x-6.3 | | [2x-3]=11 | | -0.9x+4.32=-0.4x+6.32 |